Odpowiedź :
Dane:
t=3s
s=12m
v=s/t=12m/3s=4m/s
a=v/t=4m/s / 3s = 1 1/3 m/s²
a)s=1/2a*t²= 1/2*1 1/3 m/s²*(1s)²= 2/3 m
b)a=v/t=4m/s / 3s = 1 1/3 m/s²
c)s=1/2a*t²= 1/2*1 1/3 m/s²*(2s)²= 2 2/3m
t=3s
s=12m
v=s/t=12m/3s=4m/s
a=v/t=4m/s / 3s = 1 1/3 m/s²
a)s=1/2a*t²= 1/2*1 1/3 m/s²*(1s)²= 2/3 m
b)a=v/t=4m/s / 3s = 1 1/3 m/s²
c)s=1/2a*t²= 1/2*1 1/3 m/s²*(2s)²= 2 2/3m
s - droga = vt + at²/2 = 12m
t - czas ruchu = 3s
ponieważ prędkość początkowa v = 0 to s = at²/2
a - przyspieszenie = 2s/t² = 24/9 = 2,7m/s²
a)
t = 1s
s = at²/2 = 2,7 razy 1 dzielone przez 2 = 1,34m
b)
przyspieszenie = a - przyspieszenie = 2s/t² = 24/9 = 2,7m/s²
c)
t = 2s
s = at²/2 = 2,7 razy 4 dzielone przez 2 = 5,4m
t - czas ruchu = 3s
ponieważ prędkość początkowa v = 0 to s = at²/2
a - przyspieszenie = 2s/t² = 24/9 = 2,7m/s²
a)
t = 1s
s = at²/2 = 2,7 razy 1 dzielone przez 2 = 1,34m
b)
przyspieszenie = a - przyspieszenie = 2s/t² = 24/9 = 2,7m/s²
c)
t = 2s
s = at²/2 = 2,7 razy 4 dzielone przez 2 = 5,4m